Identification of the ISWI chromatin remodeling complex of the early branching Eukaryote Trypanosoma brucei - Stanne, Tara; Shankar Narayanan, Mani; Ridewood, Sophie; Ling, Alexandra; Witmer, Kathrin; Kushwaha, Manish; Wiesler, Simone; Wickstead, Bill; Wood, Jennifer; Rudenko, Gloria (American Society for Biochemistry and Molecular Biology, 2015)
ISWI chromatin remodelers are highly conserved in eukaryotes and are important for the assembly and spacing of nucleosomes, thereby controlling transcription initiation and elongation. ISWI is typically associated with different subunits, forming specialized complexes with discrete functions. In the unicellular parasite Trypanosoma brucei, which causes African sleeping sickness, TbISWI down-regulates RNA polymerase I (Pol I) transcribed variant surface glycoprotein (VSG) gene expression sites (ESs), which are monoallelically expressed. Here, we use tandem affinity purification to determine the interacting partners of TbISWI. We identify three proteins that do not show significant homology with known ISWI-associated partners. Surprisingly, one of these is nucleoplasmin-like protein (NLP), which we had previously shown to play a role in EScontrol. In addition, we identify two novel ISWI partners, regulator of chromosome condensation 1-like protein (RCCP) and phenylalanine/tyrosine-rich protein (FYRP), both containing protein motifs typically found on chromatin proteins. Knockdown of RCCP or FYRP in bloodstream form T. brucei results in derepression of silent variant surface glycoprotein ESs, as had previously been shown for TbISWI and NLP. All four proteins are expressed and interact with each other in both major life cycle stages and show similar distributions at Pol I-transcribed loci. They are also found at Pol II strand switch regions as determined with ChIP. ISWI, NLP, RCCP, and FYRP therefore appear to form a single major ISWI complex in T. brucei (TbIC). This reduced complexity of ISWI regulation and the presence of novel ISWI partners highlights the early divergence of trypanosomes in evolution.